Antifungal, characteristic properties and composition of bee glue (propolis) - Mohd Adzim Khalili, Rohin; Aniza, Abd Aziz; Salwani, Ismail (2015)
Propolis (bee glue) has been known for centuries. It is a mixture of balsam and resins, waxes, essential oils, pollen and other substances (salivary enzymes and other compounds of bee metabolism). Due to its waxy nature and mechanical properties, bees use Propolis in the constructions and repair of their hives for sealing openings and cracks and smoothing out the internal walls and as protective barrier against external invaders like lizards, birds, snakes or against weathering threats like rain and wind. Propolis possesses a characteristic pleasant aromatic smell, it becomes soft, pliable, gummy and very sticky when heated, depending on the botanical source and time of collection, and variation exists in the color of Propolis from yellow – green to red and dark brown. More than 300 compounds are found in the Propolis which includes phenolic acids, cinnamic acid, caffeic acid, terpenes, flavonoids, esters among others; this is as a result of differences in plant source, time and location in which the Propolis is collected. The most common and widely used solvent for extraction of Propolis is ethanol. The antifungal properties of Propolis are due to its ability to act as a fungicidal and fungistatic against various fungal species. Propolis helps in wound healing, treatment of burns, ulcer, diabetes, asthma among others. Therefore, this paper reviews antifungal properties, characteristics and components of Propolis in order to serves as a reference point for further investigations.